THE CORRELATION BETWEEN FAT INTAKE AND PLASMA SUPEROXIDE DISMUTASE ACTIVITY WITH TELOMERE LENGTH OF MINANGKABAU ETHNICITY MEN, IN WEST SUMATERA, INDONESIA - AFRIWARDI, AFRIWARDI; SULASTRI, DELMI; LESTARI, YUNIAR; DESMAWATI, DESMAWATI; MINERVA, PRIMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of this research is to investigate the correlation between fat intake and plasma superoxide dismutase (SOD) enzyme activity with telomere length of Minangkabau ethnic men in West Sumatera, Indonesia. Materials and Methods: This cross-sectional study was conducted in Padang City in 2016, using a sample of 107 Minangkabau ethnic men, aged between 40 and 50 years. The total fat, saturated fatty acids (SFA), monounsaturated fatty acid (MUFA), and polyunsaturated fatty acid (PUFA) intake were collected using a food frequency questionnaire, and blood sample analysis to measure telomere length and plasma SOD activity. Results: This research indicated that an average telomere length was 584.59±305.92 bp, fat intake consists of total fat was 27.01±6.68% calorie, SFA was 24,7510.07% calorie, MUFA was 10.24±5.41% calorie, and PUFA was 7.35±3.54% calorie. Average of plasma SOD activity was 5.85±3.41 u/mL. There were no correlations between fat intake (total fat, SFA, MUFA, and PUFA) with telomere length (p>0.05), but there was a significant positive correlation between plasma SOD enzyme activity with telomere length (r=−0.202, p=0.037). Conclusion: Fat intake within normal limits does not correlate with telomere length, and plasma SOD activity is a risk factor for telomere shortening in ethnic Minangkabau men.